To factor the polynomial \(13x^{11} - 117x^3\) completely, we can first factor out the greatest common factor (GCF), which is \(13x^3\):
\[ 13x^{11} - 117x^3 = 13x^3(x^{8} - 9) \]
Next, we can observe that \(x^{8} - 9\) is a difference of squares. We can factor it as follows:
\[ x^{8} - 9 = (x^{4})^2 - 3^2 = (x^4 - 3)(x^4 + 3) \]
Putting this all together, we have:
\[ 13x^{11} - 117x^3 = 13x^3(x^{4} - 3)(x^{4} + 3) \]
Thus, the complete factorization of the given polynomial is:
\[ \boxed{13x^3(x^4 - 3)(x^4 + 3)} \]